Epidemiological importance of humans and domestic animals as reservoirs of verocytotoxin-producing Escherichia coli - Lazić Srđan; Čobeljić Miloje; Dimić Bane; Opačić Dolores; Stojanović Valentina (Vojnosanitetski Pregled, 2006)
Background/Aim. A "new" pathogenic agent, verocytotoxin - producing Escherichia coli (VTEC) emerged in the last 20 years, causing an increased number of sporadic cases, as well as of outbreaks of diarrhoeal diseases. Humans and animals can be infected with VTEC, but their epidemiological importance as a reservoir of this agent is not quite clear, especially in the Balkan region. Therefore, the aim of this study was to investigate the frequency of isolation of VTEC from the intestinal tract of humans and animals and to determine the serogroups of the isolated strains. Methods. A total of, 3 401 stool samples from humans and 2 660 samples from five different species of domestic animals were tested for the presence of this pathogen. Results. VTEC was isolated from 20 (0.6%) humans stools and from 431 (16.2%) animal fecal samples (p < 0.001). Only 15 (3.3%) VTEC strains belonged to human infection-associated serogroups (O26, O55, O111, O128 and O 157), designated as enterohaemorrhagic E. coli (EHEC). The most known serogroup- O157 was identified in 6 (1.3%) of the isolated VTEC strains; of them, 1 (5%) was of human origin and 5 (1.2%) were animal strains. Conclusion. This study revealed that domestic animals were a more important reservoir of VTEC than humans, and that the isolated VTEC strains rarely belonged to O157, as well as to other EHEC serogroups that might explain rare sporadic cases and the absence of epidemic occurrence of diarrhoeal diseases caused by VTEC in this geographic region.